2018
DOI: 10.1051/matecconf/201814403003
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement studies for cutting tools with perforated surface in turning of titanium alloy

Abstract: Abstract:In turning process, the cutting tool is essential for shaping materials. The cutting tools with various perforated surfaces help to increase the cutting tool life. Also, advances in CNC machining technologies have enhanced the productivity of machining process. One of the best or futuristic approaches in modern manufacturing engineering is the use of FEM Simulation for the metal cutting process. FEM simulation helps in understanding the metal deformation process and also helps in the reduction of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…For instance, few studies have reported an improvement in the tribological properties of the material under various cooling agents [2][3][4][5]. Cutting fluids are frequently used in most of the machining processes in order to reduce the friction and to improve the wear properties [6].One of the environmentally sustainable lubrication methods which can be used in improving the performance of machining is MQL (Minimum Quantity Lubrication). The previous studies on machining show notable improvements in the machinability of the materials [7][8][9][10] through MQL technique.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, few studies have reported an improvement in the tribological properties of the material under various cooling agents [2][3][4][5]. Cutting fluids are frequently used in most of the machining processes in order to reduce the friction and to improve the wear properties [6].One of the environmentally sustainable lubrication methods which can be used in improving the performance of machining is MQL (Minimum Quantity Lubrication). The previous studies on machining show notable improvements in the machinability of the materials [7][8][9][10] through MQL technique.…”
Section: Introductionmentioning
confidence: 99%